Methodology for assessing and controlling the risk grade of structural columns threatened by blast incident - Sun, Peng; Hou, Xiaomeng (Journal of Civil Engineering and Management, 2025)
Columns are important structural components and are threatened by local conflicts and explosion accidents. This paper presents a fuzzy-based risk assessment framework to evaluate the potential blast disasters associated with structural columns. The framework establishes an indicator system and incorporates risk functions and a fuzzy transformation system for blast risk assessment. The priority weights of critical attributes are determined using a fuzzy analytic hierarchy process (FAHP) approach, and the risk factor (RF) is calculated via the aggregation of foundational fuzzy evaluations. The feasibility and applicability of the framework are demonstrated through the risk level assessment of five example columns. The framework’s rationality is further validated by comparing the onrisk grades of identical cases, as assessed by the proposed framework and alternative methods. The study results indicated that the framework can effectively discern the risk range of desired grade rankings and ascertain the risk grade. By integrating the obtained attribute ranking and hierarchical structure, the framework facilitates the identification of potent strategies for controlling blast risk. The resulting risk-grade findings serve as a foundation for the identification of priority protection and anti-explosion design of structural columns.